Scooby-Doo! and the tank of terrors - Sander, Sonia (Herman, Gail, 1959- Scooby-Doo readers ;, 2012)
"A ghost diver is haunting the local aquarium. Now it's up to Scooby and his friends to unmask that spooky snorkeler!"--Publisher.